Analysis of a Mid Rise Structure Considering Floating Column with Different Arrangements of Beams below using staad.pro - Awaneesh Nema; Vedant Shrivastava (International Journal of Scientific Research in Civil Engineering, 2021)
Floating columns are one of the important aspects of multi-storey structures due to their various advantages thus seem to be unavoidable. Floating columns are generally not found reliable in seismic prone areas. This research is followed towards analyzing the performance of floating columns structure considering different beam arrangements  prone to seismic load. The research was focused on analyzing the effects of floating columns when supported on various pattern of beams in a G+6 storey structure in considering seismic zones III and soft soil condition using Staad.Pro.v8i. The analysis of floating columns was done considering the parameters namely the base shear, storey displacement, storey drift and storey acceleration concerning subject multi-storey structure with different placement of supporting beam just below the floating columns.
Keywords: Floating Columns; STAAD.Pro; Story Drift; Base Shear; Story Displacement